Mucoadhesive Polymeric Platform for Drug Delivery; A Comprehensive Review - Agarwal, Shweta; Aggarwal, Shikha (Current Drug Delivery, 2015)
Mucoadhesion can be defined as adhesion in biological setting. Process of mucoadhesion takes place in 3 stages- the first stage being that of wetting or swelling of mucoadhesive polymer. Second stage involves interpenetration of the chains of mucoadhesive polymer and the third stage involves formation of chemical bonds between entangled chains. Several polymer related factors like molecular weight, chain length, degree of cross-linking, hydration, functional groups, charge, polymer concentration and several environmental and physiological factors like contact time, mucin turnover rate and mucus viscosity affect the degree of mucoadhesion. Formulation scientists have structured and engineered several mucoadhesive polymers for their usefulness in enhancement of bioavailability, controlled and targeted drug delivery. Mucoadhesive polymers can be classified as non-specific first generation polymers and novel second generation polymers based on the mechanism of mucoadhesion. Mucoadhesive drug delivery systems have been applied to buccal cavity, oesophagus, gastrointestinal tract, eye, nasal cavity, vagina and rectal cavity. Several in vitro/ex vivo and in vivo evaluation techniques have evolved for the evaluation of mucoadhesive strength of these polymers. This review provides historical perspective on mucoadhesive polymers and an understanding of the phenomenon of mucoadhesion, factors affecting mucoadhesion, types of mucoadhesive polymers, their practical applications and the various evaluation techniques for determination of mucoadhesive strength.
Keywords: mucous membrane